The Effect Of English Speech Assistant Application On Second Grade Arabic Speaking Students - Hamed, Qahtan Mushrif; Abraheem, AbdalQadir Khalid (Ijaz Arabi Journal of Arabic Learning, 2025)
This study examines how the ELSA Speak app improves second-grade Arab students' English-speaking competency at Alfaruq Intermediate and quantifies the improvement. It aims to show the students' ability and performance in the second intermediate school. The study included one English teacher and 15 second-graders. A Classroom Action Research (CAR) approach, combined with qualitative and quantitative methods, was adopted to analyze the data. Qualitative data were collected using observation checklists, whereas quantitative data were obtained by comparing students' pre- and post-tests. The first cycle is 5.501, the second 7.663. Initial-cycle post-assessment. The post-test means of 62.43 and 52.71 exceeded pre-test scores. In the second cycle, the post-test mean exceeded the pre-test. After test II, the score was 73.91, up from 61.32. Students' progress shows improvement. KKM passing graders improved 13.34% in the first cycle and 60% in the second. These findings show that the ELSA Speak app improves Arabic-speaking students' English-speaking skills.